Seguimiento a egresados de un programa de odontología, estado laboral - Morales Ospina, Diana Marcela (Universidad Antonio Nariño, 2023)
To identify the current situation of dentistry graduates in relation to their employment situation at the Antonio Nariño Palmira University.